Pengelolaan Aset Daerah Taman Hutan Kota dan Taman Satwa Oleh Pemerintah Kabupaten Pasaman Barat - Chandra, Pivit Septiary; Ilosa, Abdiana; Fabiola, Elva; abdiana, ella (LPPM Universitas Ekasakti, 2022)
This research was conducted at the Environmental Service of West Pasaman Regency. The purpose of this study was to find out how the management of regional assets for the City Forest Park and Animal Park by the West Pasaman district government. The method used in this research is descriptive with a qualitative approach. While the data collection techniques were carried out through the methods of observation, interviews and documentation as well as sampling techniques, namely people who were considered to know the things to be studied. Based on the research conducted, it can be seen that the management of regional assets for urban forest parks and animal parks by the West Pasaman district government has not run optimally starting from management, maintenance and development, no action has been taken due to several factors, namely the transfer of the authority of the Forestry Service to the province resulting in a budget funds for urban forest parks and animal parks are not clear, Covid-19 and the change of regional heads. This is evidenced by the results of interviews with officials from the Environmental Service and the rangers of urban forest parks and animal parks.